Kaip Mes Žaide˙me Revoliucija . How We Played the Revolution - Žickytė, Giedrė (Vildžiūnaitė, Dagnė, 2011)
Verzio9 FF Submission. Duration: 01:07:00 The story begins in 1984, the very beginning of perestroika in the USSR, when a group of architects in Kaunas, Lithuania decided to put on a one-night gig as a New Year party prank. The joke went so well that rumors about the exciting new rock band Antis began to spread. The impressive make-up and props, the stylized showmanship and lyrics added up to a pervasive caricature of Soviet propaganda and perfectly discredited the absurdity of Soviet reality. Soon the group's intellectual clowning spawned the Rock Marches – massive events involving thousands of people. These turned into the great assemblies for Lithuanian independence that later became known as the Singing Revolution. This is a story about a small country that made headlines right across the world.